2018
DOI: 10.7717/peerj.5658
|View full text |Cite
|
Sign up to set email alerts
|

A secretory hexokinase plays an active role in the proliferation of Nosema bombycis

Abstract: The microsporidian Nosema bombycis is an obligate intracellular parasite of Bombyx mori, that lost its intact tricarboxylic acid cycle and mitochondria during evolution but retained its intact glycolysis pathway. N. bombycis hexokinase (NbHK) is not only a rate-limiting enzyme of glycolysis but also a secretory protein. Indirect immunofluorescence assays and recombinant HK overexpressed in BmN cells showed that NbHK localized in the nucleus and cytoplasm of host cell during the meront stage. When N. bombycis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…Microsporidia hexokinases have gained a signal peptide and were experimentally shown to be secreted in several species [19,[44][45][46]. This enzyme potentially increases host metabolism to provide nutrients for the developing parasites, and consistent with this idea, knockdown of the enzyme reduces microsporidia proliferation [44]. To obtain ATP from their hosts, microsporidia encode a nucleotide transport protein that was likely acquired via horizontal gene transfer from bacteria.…”
Section: How Have Microsporidia Adapted To Their Hosts?mentioning
confidence: 91%
See 1 more Smart Citation
“…Microsporidia hexokinases have gained a signal peptide and were experimentally shown to be secreted in several species [19,[44][45][46]. This enzyme potentially increases host metabolism to provide nutrients for the developing parasites, and consistent with this idea, knockdown of the enzyme reduces microsporidia proliferation [44]. To obtain ATP from their hosts, microsporidia encode a nucleotide transport protein that was likely acquired via horizontal gene transfer from bacteria.…”
Section: How Have Microsporidia Adapted To Their Hosts?mentioning
confidence: 91%
“…This work allowed the identification of a conserved, microsporidia-specific ribosomal protein (msL1) and also identified two conserved microsporidia dormancy factors, one that is conserved throughout eukaryotes (MDF1) and the other that was only found in several species of microsporidia (MDF2) [14]. Although it is currently not possible to genetically modify microsporidia, using RNAi to knockdown genes provides a powerful approach to directly study microsporidia protein function in the context of infection [44,49]. Finally, the discovery of microsporidia that infect model organisms such as C. elegans and Drosophila melanogaster provides easily cultured, genetically tractable hosts for studying how microsporidia function [2,19,35,50].…”
Section: Future Perspectivementioning
confidence: 99%
“…Hexokinase from microsporidia has acquired signal peptides (Cuomo et al, 2012), and has been demonstrated to be secreted into host cells by several species ( N. parisii , Nematocida ausubeli , T.hominis , N . bombycis and A. locustae ) (Ferguson & Lucocq, 2018; Huang et al, 2018; Reinke et al, 2017; Senderskiy et al, 2014; Timofeev, Senderskiy, Tsarev, Tokarev, & Dolgikh, 2017). Localisation of these proteins has been observed in the extracellular coat of the meront, the host cytoplasm, as well as the host nucleus, suggesting a potential role in regulating transcription (Huang, Zheng, et al, 2018; Senderskiy et al, 2014).…”
Section: Microsporidia Use Secreted Proteins To Interact With Its Hostmentioning
confidence: 99%
“…bombycis and A. locustae ) (Ferguson & Lucocq, 2018; Huang et al, 2018; Reinke et al, 2017; Senderskiy et al, 2014; Timofeev, Senderskiy, Tsarev, Tokarev, & Dolgikh, 2017). Localisation of these proteins has been observed in the extracellular coat of the meront, the host cytoplasm, as well as the host nucleus, suggesting a potential role in regulating transcription (Huang, Zheng, et al, 2018; Senderskiy et al, 2014). Microsporidia hexokinases can phosphorylate glucose with enzymatic properties similar to other hexokinases, suggesting that this enzyme is secreted to phosphorylate host glucose, which is then taken up by the parasite cell (Dolgikh, Tsarev, Timofeev, & Zhuravlyov, 2019).…”
Section: Microsporidia Use Secreted Proteins To Interact With Its Hostmentioning
confidence: 99%
See 1 more Smart Citation